2004
DOI: 10.1002/cne.20169
|View full text |Cite
|
Sign up to set email alerts
|

Localization of neurokinin 1 receptor (NK1R) immunoreactivity in rat esophagus

Abstract: The aim of the present immunohistochemical study was to investigate the localization of neurokinin 1 receptor (NK1R) in rat esophagus and examine the relationship between NK1Rs and intrinsic cholinergic, nitrergic, or substance P (SP) neurons. NK1R immunoreactivity (IR) was observed on the nerve cell bodies in the myenteric ganglia throughout the esophagus, but not on striated muscles and smooth muscle cells of the muscularis mucosae. The frequency of occurrence of NK1R neurons was highest in the cervical esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The antiserum recognizes a single band of approximately 68-70 kDa molecular weight on western blots of mouse brain (Chemicon datasheet), and has been used by others to stain the cholinergic terminals and neurons of the myenteric plexus in rats and guinea pigs (Mawe et al, 1996; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). ChAT is commonly used for detecting parasympathetic cholinergic preganglionic terminals as well as a subset of postganglionic myenteric neurons (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). In our samples, the antiserum produced a staining pattern identical to previous reports (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiserum recognizes a single band of approximately 68-70 kDa molecular weight on western blots of mouse brain (Chemicon datasheet), and has been used by others to stain the cholinergic terminals and neurons of the myenteric plexus in rats and guinea pigs (Mawe et al, 1996; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). ChAT is commonly used for detecting parasympathetic cholinergic preganglionic terminals as well as a subset of postganglionic myenteric neurons (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). In our samples, the antiserum produced a staining pattern identical to previous reports (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006).…”
Section: Methodsmentioning
confidence: 99%
“…ChAT is commonly used for detecting parasympathetic cholinergic preganglionic terminals as well as a subset of postganglionic myenteric neurons (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). In our samples, the antiserum produced a staining pattern identical to previous reports (Mawe et al, 1996; Mann et al, 1999; Schicho et al, 2001; Miampamba et al, 2002; Kuramoto et al, 2004; 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Since vagal primary afferent fibers (Berthoud et al, 1997) and at least the majority of enteric neurons in the rat esophagus are capsaicinresistant, the most likely source for the capsaicin-sensitive nerve fibers are spinal ganglia (Holzer, 1988). Spinal primary afferents from esophagus and gastrointestinal tract typically coexpress SP, NKA, and CGRP (for references see Rodrigo et al, 1985;Holzer, 1988;Holzer and Holzer-Petsche, 1997a, b;Dü tsch et al, 1998;Kuramoto et al, 2004). Tachykinins and CGRP released from primary afferents mediate their ''local effector'' function (Holzer, 1988).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Tachykinins and CGRP released from primary afferents mediate their ''local effector'' function (Holzer, 1988). Spinal afferent nerve fibers were shown to closely contact myenteric neurons in the esophagus (Mazzia and Clerc, 1997), and myenteric neurons in the esophagus express NKA receptors (Kuramoto et al, 2004). Thus, key elements of a local reflex arc from capsaicin-sensitive afferents via nitrergic myenteric neurons to motor endplates are present in the esophagus.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…In these models, the capsaicin‐triggered inhibition of vagally induced striated muscle contractions was significantly, though not completely, reduced by the NOS blocker N G‐nitro‐ l ‐arginine methyl ester (l ‐NAME) and in preparations pretreated with tachykinin receptor antagonists, and was abrogated in neonatally capsaicin‐treated animals 5–7 . This indicated that capsaicin stimulated transient receptor potential vanilloid type 1 (TRPV1) expressing tachykininergic neurons, most likely primary afferents, that in turn excited nitric oxide (NO) releasing co‐innervating neurons via neurokinin‐1 (NK‐1) receptors 8 . The incomplete reduction of the capsaicin‐triggered inhibition by l ‐NAME suggested involvement of synergistic co‐transmitters, e.g.…”
Section: Introductionmentioning
confidence: 99%